Improving the Pedagogical Skills of PASS Leaders on the Job with Synchronous Feedback: A Feasibility Study - Taylor, Louise; Dekker, Izaak (Teaching and Learning Inquiry, 2025)
Peer assisted study sessions (PASS), also known as supplemental instruction, are structured peer guided sessions linked to a specific course, led by experienced and trained students called PASS-leaders. These PASS-leaders undergo several days of training before running their first session and receive supervision and feedback “on the job.” Research suggests that training improves student outcomes whereby supervision is considered best practice, as required by PASS protocols. However, it is unclear what type of supervision best supports PASS-leaders. Thus far, studies have not compared different methods for on-the-job training. Current practice involves supervisors observing PASS sessions without intervening but providing post hoc feedback. While this prevents undermining the PASS leaders, it delays their ability to act on feedback. This study, carried out at an institution for initial teacher education, developed and tested a method for providing immediate feedback using a bug-in-ear device linked to a live-stream. Six PASS-leaders were observed during four to six sessions each, receiving either synchronous feedback with a bug-in-ear or in-person asynchronous post hoc feedback. In group interviews PASS-leaders reported appreciating the immediacy of synchronous feedback which allowed them to act in real-time. The surveys after each lesson indicated that they felt significantly more confident about teaching following live feedback. They described the supervisor as an invisible helper, providing support or assistance. Because the bug-in-ear method could only provide feedback on visible instructional and pedagogical actions, both PASS-leaders and PASS-supervisors recommended using this as a supplement to a pre-session briefing and a post-session debrief.